2019
DOI: 10.1016/j.cell.2019.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Fc Glycan-Mediated Regulation of Placental Antibody Transfer

Abstract: Graphical Abstract Highlights d NK cell-activating antibodies are selectively transferred across the placenta d Digalactosylated Fc glycans are preferentially transferred across the placenta d Digalactosylated antibodies bind more effectively to FcRn and FCGR3A d Although immature, neonatal NK cells are highly responsive to immune complexes SUMMARY Despite the worldwide success of vaccination, newborns remain vulnerable to infections. While neonatal vaccination has been hampered by maternal antibody-mediated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
231
5
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 184 publications
(261 citation statements)
references
References 63 publications
22
231
5
3
Order By: Relevance
“…Here, using a variety of in vitro and in vivo approaches, we addressed questions also asked by recent studies as to whether FcγRs may be involved in transplacental transfer of human IgGs (9,14,15). Unlike some studies (14,15) but consistent with other (9), we find that there is no enrichment for specific Fc glycoforms in cord blood over paired maternal blood.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Here, using a variety of in vitro and in vivo approaches, we addressed questions also asked by recent studies as to whether FcγRs may be involved in transplacental transfer of human IgGs (9,14,15). Unlike some studies (14,15) but consistent with other (9), we find that there is no enrichment for specific Fc glycoforms in cord blood over paired maternal blood.…”
Section: Discussionmentioning
confidence: 60%
“…Galactosylation has been observed to increase Fc-FcγRIIIa binding, but only in absence of fucosylation (25). Recently, it has been reported that IgG galactosylation, in the presence of fucosylation, impacts IgG binding to FcγRIIIa and FcRn (14). Given these contrasting reports on the role of Fc galactosylation in modulating FcγR and FcRn affinity, we performed a comprehensive analysis of the FcγR and FcRn affinity of IgG Fc glycoforms with defined, homogenous glycan structures.…”
Section: Galactosylation Of Igg Fc Does Not Significantly Impact Bindmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations are in line with the gradual replacement of maternal with infant antibodies. Altered glycosylation during pregnancy and preferential transplacental transfer result in increased IgG Fc‐galactosylation of maternal antibodies . In addition, like all adult antibodies, maternal antibodies have lower fucosylation (94%) compared to highly fucosylated infant antibodies, which reach adult levels around the age of 20 years …”
Section: Discussionmentioning
confidence: 99%
“…Altered glycosylation during pregnancy and preferential transplacental transfer result in increased IgG Fc-galactosylation of maternal antibodies. 35,36,64 In addition, like all adult antibodies, maternal antibodies have lower fucosylation (94%) compared to highly fucosylated infant antibodies, which reach adult levels around the age of 20 years. 35 Surprisingly, we observed similar correlations between glycosylation and age for RSV-specific antibodies.…”
Section: Discussionmentioning
confidence: 99%